Overexpression of the HDA15 Gene Confers Resistance to Salt Stress by the Induction of NCED3, an ABA Biosynthesis Enzyme - Truong, Hai An; Lee, Seokjin; Trịnh, Cao Son; Lee, Won Je; Chung, Eui-Hwan; Hong, Suk-Whan; Lee, Hojoung (Frontiers in Plant Science, 2021)
Salt stress constitutes a major form of abiotic stresses in plants. Histone modification plays an important role in stress tolerance, with particular reference to salt stress resistance. In the current study, we found that HDA15 overexpression confers salt stress resistance to young seedling stages of transgenic plants. Furthermore, salt stress induces HDA15 overexpression. Transcription levels of stress-responsive genes were increased in transgenic plants overexpressing HDA15 (HDA15 OE). NCED3, an ABA biosynthetic gene, which is highly upregulated in HDA15 transgenic plants, enhanced the accumulation of ABA, which promotes adaptation to salt stress. ABA homeostasis in HDA15 OE plants is maintained by the induction of CYP707As, which optimize endogenous ABA levels. Lastly, we found that the double mutant HDA15 OE/ hy5 ko plants are sensitive to salt stress, indicating that interaction between HDA15 and HY5 is crucial to salt stress tolerance shown by HDA15 OE plants. Thus, our findings indicate that HDA15 is crucial to salt stress tolerance in Arabidopsis.